2017
DOI: 10.1055/s-0036-1584402
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a Combined Maxillectomy and Segmental Mandibulectomy Defect in a Seven-Year-Old with a Single Free Fibula Osteocutaneous Flap

Abstract: Vascularized bone flaps form an integral part of head and neck reconstruction. Nevertheless, the best results in complex head and neck defects are far from optimal. A combined defect involving the maxilla and mandible may ideally require two bone flaps for reconstruction. The purpose of this article is to report a case of single-stage bony reconstruction of a combined maxilla and mandible defect after a benign tumor excision in a 7-year-old girl, using a free fibula flap. This case is unique in many aspects su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Among reported cases during the follow-up period, 3 patients (2.8%) with benignindications and 2 patients (5.9%) with malignant indications exhibited disease recurrence (Supplementary Digital Content, Table 5, http://links.lww.com/SCS/D797). All studies reviewed are shown in Supplementary Digital Content, Table 6, 17-61 http://links.lww.com/SCS/D798.…”
Section: Resultsmentioning
confidence: 99%
“…Among reported cases during the follow-up period, 3 patients (2.8%) with benignindications and 2 patients (5.9%) with malignant indications exhibited disease recurrence (Supplementary Digital Content, Table 5, http://links.lww.com/SCS/D797). All studies reviewed are shown in Supplementary Digital Content, Table 6, 17-61 http://links.lww.com/SCS/D798.…”
Section: Resultsmentioning
confidence: 99%
“…Fibula free flaps are the workhorse for composite reconstructive defects as they provide osseous and soft tissue components, with the fibula providing ample bony length to reconstruct multi-component defects of the midface and lower facial skeleton. 1,7 Additionally, the bone of fibula free flaps can facilitate dental rehabilitation with implants. 6 The outcomes of fibula free flaps for the reconstruction of large facial defects in the adult population have welldefined functional and cosmetic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The paradigm for treatment in the adult population is well‐defined with autologous composite free tissue transfer that replaces the composite tissue defect. Fibula free flaps are the workhorse for composite reconstructive defects as they provide osseous and soft tissue components, with the fibula providing ample bony length to reconstruct multi‐component defects of the midface and lower facial skeleton 1,7 . Additionally, the bone of fibula free flaps can facilitate dental rehabilitation with implants 6 …”
Section: Introductionmentioning
confidence: 99%
“… 2 The fibula osteo-cutaneous flap is used for reconstruction of many anatomical defects. They are used in reconstruction of mandible, maxilla, 3 clavicle, 4 long bones (humerus, radius, ulna, femur, tibia), 5 vertebrae, calcaneum, 6 etc. The length of the bone that can be harvested, presence of muscle, and large skin paddle that can be harvested have added to the advantages of using fibula flap for reconstruction purposes.…”
Section: Introductionmentioning
confidence: 99%